An exploratory study of personal financial wellbeing determinants: examining the moderating effect of gender - Falahati, Leila; Sabri, Mohamad Fazli (Canadian Center of Science and Education, 2015)
Financial educators have placed importance on the study of the determinants of financial wellbeing for some decades now. The subject of the research has comprised factors such as marital status, employment status, education, income and health, which impact on financial wellbeing. However, there is as yet, a lack of research on the perceived influence of differences in financial wellbeing between the genders, particularly within the Asian context. The present research evaluates the moderating effect of gender on the determinants of financial wellbeing among college students in Malaysia. Samples for this study comprised students in Malaysian universities. The multi stage stratified random sampling technique was utilized to select the respondents, while self-administered questionnaires were used to collect the data. Further, a multi-group analysis approach using AMOS was used in studying the influence of gender on financial wellbeing. The findings of the present research show that among college students, gender has a substantial moderating effect on the factors related to financial wellbeing.